Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b
\(\left|6+x\right|\ge0;\left(3+y\right)^2\ge0\Rightarrow\left|6+x\right|+\left(3+y\right)^2\ge0\)
Suy ra \(\left|6+x\right|+\left(3+y\right)^2=0\)\(\Leftrightarrow\hept{\begin{cases}6+x=0\\3+y=0\end{cases}\Leftrightarrow}\hept{\begin{cases}x=-6\\y=-3\end{cases}}\)
a
Ta có:\(\left|3x-12\right|=3x-12\Leftrightarrow3x-12\ge0\Leftrightarrow3x\ge12\Leftrightarrow x\ge4\)
\(\left|3x-12\right|=12-3x\Leftrightarrow3x-12< 0\Leftrightarrow3x< 12\Leftrightarrow x< 4\)
Với \(x\ge4\) ta có:
\(3x-12+4x=2x-2\)
\(\Rightarrow5x=10\)
\(\Rightarrow x=2\left(KTMĐK\right)\)
Với \(x< 4\) ta có:
\(12-3x+4x=2x-2\)
\(\Rightarrow10=x\left(KTMĐK\right)\)
a) \(4x^2\left(x-2\right)-x+2=0\)
\(\Leftrightarrow4x^2\left(x-2\right)-\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(4x^2-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-2=0\\4x^2-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2\\x=\pm\frac{1}{2}\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=2\\x=\pm\frac{1}{2}\end{cases}}\)
g) \(x^2-7x+10=0\)
\(\Leftrightarrow\left(x-5\right)\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\x-2=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=5\\x=2\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=5\\x=2\end{cases}}\)
a)(2x-3)2=1<=> \(\orbr{\begin{cases}2x-3=1\\2x-3=-1\end{cases}< =>\orbr{\begin{cases}2x=4\\2x=2\end{cases}}}\)\(< =>\orbr{\begin{cases}x=2\\x=1\end{cases}}\)
x=2 =>22.52=20y.5y <=>100 = 100y <=> y=1
x=1 => 2.5= 20y.5y <=>10=100y <=>y = 1/2
b)(4x-3)2+(y2-9)2\(\ge0\)
dấu = sảy ra khi \(\hept{\begin{cases}4x-3=0\\y^2-9=0\end{cases}< =>\hept{\begin{cases}4x=3\\y^2=9\end{cases}}}\)\(\hept{\begin{cases}x=\frac{3}{4}\\y=\pm3\end{cases}}\)
c) <=> (y-5)8 \(\le-\left(x+4\right)^7\) (1)
(y-5)8 >=0 với mọi y nên -(x+4)7 \(\ge\left(y-5\right)^8\ge0\)<=> (x+4)7\(\le0< =>x+4\le0< =>x\le-4\)
Khi đó (1) <=> y-5\(\le\sqrt[8]{-\left(x+4\right)^7}\) <=> y\(\hept{\begin{cases}y\le5-\sqrt[8]{-\left(x+4\right)^7}\\x\le-4\end{cases}}\)
Ta có: x2+4x-x-4=0
=>x2+2.2.x+4-4-x-4=0
=>x2+2.2.x+2x-x-8=0
=>(x+2)2-x-2-6=0
=>(x+2).(x+2)-(x+2)=0+6
=>(x-2).(x+2-1)=6
=>(x+2).(x+1)=6=3.2
=>(x+2).(x+1)=(1+2).(1+1)
=>x=1